PENGARUH KOMPETENSI KARYAWAN DAN KINERJA PELAYANAN STAF FRONT OFFICE TERHADAP KEPUASAN PELANGGAN HOTEL BINTANG 3, 4, DAN 5 DI KOTA BANDUNG DAN SEKITARNYA - Kanaidi, Kanaidi; Andranaswari, Nisrina (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2021)
This study aims to determine the effect of employee competence and service performance of front office staff on customer satisfaction at 3, 4, and 5 star hotels in Bandung and its surroundings. This study uses a survey method with descriptive and verification analysis. Hypothesis testing using path analysis. Determination of the sample using purposive sampling. Data were obtained by distributing questionnaires to 150 respondents, who were hotel guests and or who were had stayed at 3, 4 and 5 star hotels in Bandung and its surroundings. The questionnaire has been tested for validity and reliability first. Secondary data obtained through literature review of various relevant literature. The results of the descriptive analysis concluded that the overall competence of hotel employees was judged by the customer to be in the good category. However, there are still some indicators that are considered weak. The service performance of the hotel's front office staff as a whole is considered by customers to be still in the fairly good category and there are still some indicators that are considered adequate, some are even considered not good. The overall level of hotel customer satisfaction is also considered by customers to be still in the fairly good category. The results of the verification analysis show that employee competence and service performance of hotel front office staff have a positive effect on customer satisfaction at 3, 4 and 5 star hotels in Bandung City and its surroundings. Employee competence, service performance of front office staff, and customer satisfaction are deemed to need the attention of hotel management to be improved and improved, through various ways that have been described in the suggestions section.Keywords: employee competence, service performance, front office staff, customer satisfaction.